2000
DOI: 10.1093/geront/40.5.549
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Press and Adaptation to Disability in Hospitalized Live-Alone Older Adults

Abstract: The increased understanding of adaptation in live-alone older adults with a new-onset disability is particularly timely given the increase in live-alone older adults and the dire consequences associated with change in living arrangement (i.e., mortality and morbidity) in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 44 publications
(51 reference statements)
1
27
0
1
Order By: Relevance
“…They reported more difficulties in the IADL skills of transportation and shopping. The findings concurred with those of Lichtenberg, MacNeill, and Mast (2000). In their study of the living-alone status of older adults (m = 73.75 years old) who were three and six months' posthospital discharge, the strongest predictor of living situation was functional independence, particularly IADL.…”
Section: Discussionsupporting
confidence: 82%
“…They reported more difficulties in the IADL skills of transportation and shopping. The findings concurred with those of Lichtenberg, MacNeill, and Mast (2000). In their study of the living-alone status of older adults (m = 73.75 years old) who were three and six months' posthospital discharge, the strongest predictor of living situation was functional independence, particularly IADL.…”
Section: Discussionsupporting
confidence: 82%
“…A possible explanation for these findings is that healthy widowed men live alone, but experience problems in IADLs, and those having more severe problems (mobility or BADL disability) live with others, because they need help performing ADLs. Also, from earlier studies, it is known that people with more disabilities more often live with others, 26,27 but some other studies showed better health in those living with others than those living alone. 28,29 Although those results and the results of the present study seem contradictory, differences in the order of causality might explain the differences; those who are already dependent in several activities might start living with others (present study), whereas those who already live with others will develop fewer health problems than those living alone.…”
Section: Discussionmentioning
confidence: 99%
“…If persons are to live successfully in the community after hospitalization for a disabling illness, projections of their eventual functionality must occur within the contexts of their home architecture and available social supports. Providing meaningful consultation and developing an individualized plan of care for those who receive care in an inpatient rehabilitation facility will be particularly challenging for people who will be living alone [42]. …”
Section: The Biopsycho-ecological Modelmentioning
confidence: 99%